2018
DOI: 10.1177/1079063218791176
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Leuprolide Acetate in the Management of High-Risk Sex Offenders

Abstract: The present study investigates whether leuprolide acetate (Lupron) adds to the efficacy of traditional sex offender treatment. A group of sex offenders receiving both Lupron and cognitive behavioral therapy (CBT; n = 25) were compared with a group of sex offenders receiving only CBT ( n = 22). Treated subjects were compared with norms available with reference to the Static-99R, as well as compared with a sample of untreated, nonsexual violent offenders ( n = 81), to provide baseline data regarding risk of viol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…An unpublished study was identified through personal contact with a scientific journal. 60 Information on the number of patients, their diagnoses, the applied dose of the LHRH agonist, and any side effects occurring under LHRH agonist treatment is presented in Table 1. Furthermore, the WFSBP published clinical guidelines on the pharmacologic treatment of adolescent and adult sexual offenders.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An unpublished study was identified through personal contact with a scientific journal. 60 Information on the number of patients, their diagnoses, the applied dose of the LHRH agonist, and any side effects occurring under LHRH agonist treatment is presented in Table 1. Furthermore, the WFSBP published clinical guidelines on the pharmacologic treatment of adolescent and adult sexual offenders.…”
Section: Resultsmentioning
confidence: 99%
“…59 For the 1st time, the rate of recidivism was compared between a group of sexual offenders being treated with LHRH agonists and cognitive-behavioral therapy (CBT; n ¼ 25) and a group of sexual offenders being treated with CBT only (n ¼ 22). 60 All sexual offenders receiving LHRH agonists were diagnosed with a paraphilic disorder and they had a significantly higher risk measured with the Static-99R compared with the CBT-only group. 60,82 All sexual offenders were treated in a community treatment program.…”
Section: Leuprolidementioning
confidence: 99%
See 1 more Smart Citation
“…A recent quasi-experimental study was able to show that the 25 individuals who committed a sexual offense and who have been treated with a combination of GnRH-agonists and cognitive behavioral therapy had a lower recidivism rate than the 22 individuals from the comparison group who were treated with cognitive behavioral therapy only ( Gallo et al, 2018 ). While none of the patients who had been treated with GnRH-agonists reoffended sexually during the follow-up period ( M = 5.7 years, SD = 2.2 years), one individual in the psychotherapy-only group (follow-up period: M = 6.4 years, SD = 2.0) committed a sexual reoffense although patients in the GnRH-agonist group had a significantly higher initial risk level.…”
Section: Empirical Findings On the Efficacy Of Tlm Treatmentmentioning
confidence: 99%
“…A recent Swedish study investigated the efficacy of methylphenidate in the treatment of attention deficit hyperactivity disorder and drug relapse in criminal offenders with substance dependence released to the community (Konstenius et al 2014). A Canadian study (Gallo et al 2019) reported on a long-term outcome study on depotleuprolide acetate administration using officially recorded recidivism as the primary dependent measures. Such studies suggest that the field is innovating and advancing and that there will be increasing scientific interest in and support for the pharmacological treatment of paraphilic disorders.…”
Section: Commentary On Guidelines For the Pharmacological Treatment Omentioning
confidence: 99%